Customs Administration Reform and Modernization in anglophone Africa : Early 1990's to Mid-2010 - Zake, Justin (IMF Working Papers; Working Paper ;, 2011)
Anglophone African countries have been implementing reform and modernization initiatives in their Customs administrations. This paper outlines the progression of key reform and modernization initiatives in these countries since the early 1990s, and assesses the gap between these reforms and those of more modern Customs agencies. The review suggests that Customs administration reform and modernization initiatives in Anglophone African countries generally lag behind international good practice and it is necessary to speed up implementation if revenue, trade facilitation, and trade chain security objectives are to be achieved. The findings also have implications on the design of reform programs and focus of potential technical assistance for the outstanding reform agenda.